Intranasal IL-4 Administration Alleviates Functional Deficits of Periventricular Leukomalacia in Neonatal Mice - Yu, Lin-chao; Miao, Jing-kun; Li, Wei-bin; Chen, Na; Chen, Qi-xiong (Frontiers in Neurology, 2020)
Abstract Background Periventricular leukomalacia (PVL) is the major form of brain injury in premature infants. Currently, there are no therapies to treat PVL. Several studies suggested that polarization of microglia, a resident macrophage-like immune cell in the central nervous system, plays a vital role in brain injury and recovery. As an important mediator of immunity, Interleukin-4 (IL-4) has critical effects on many immune cells, such as astrocytes and microglia. Increasing evidence shows that IL-4 plays a well-established role in attenuating inflammation in neurological disorders. Additionally, as a noninvasive and highly effective method, intranasal drug administration is gaining increasing attention. Therefore, in our study, we hypothesized that intranasal IL-4 administration is a promising strategy for PVL treatment. Methods The therapeutic effects of IL-4 on neuroprotection were evaluated using a Control group, Hypoxia group, and Hypoxia + IL-4 treatment group. The PVL mouse model was established by a severe, acute hypoxia (SAH) protocol. Exogenous IL-4 was intranasally administered to investigate its neuroprotective effects. A functional study was used to investigate neurological deficits, immunohistochemical technology and western blotting were used to detect protein levels, and electron microscopy was used to evaluate myelination. Results The results suggested that hypoxia stimulated Iba1+ microglial activation, downregulated myelin-related gene (NG2, MAG, and MBP) expression, reduced MBP protein levels, and caused neurological deficits. However, the intranasal administration of exogenous IL-4 partially inhibited Iba1+ microglial activation, improved myelination, and alleviated neurological deficits. The mechanistic study showed that IL-4 improved myelination possibly through the IL-4Ra-mediated polarization of microglia from the M1 phenotype to the M2 phenotype. Conclusion In summary, our findings demonstrated that the intranasal administration of exogenous IL-4 improves myelination and attenuates functional deficits in a hypoxia-induced PVL model. Intranasal IL-4 administration may be a promising strategy for PVL treatment, for which further mechanistic studies are urgent.